PENGEMBANGAN ASESMEN DIGITAL BERBASIS GAME EDUKASI PADA MATA PELAJARAN IPAS KELAS V SEKOLAH DASAR - Hanaviah, Suci; Rahmi Pratiwi; Rosmaria; Khairul Alfahani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to develop and examine the validity, practicality, and effectiveness of a digital assessment based on educational games for the Natural and Social Sciences (IPAS) subject on food-chain material for fifth-grade elementary school students. The study was motivated by conventional classroom practices, low student engagement, and summative assessment that provided little formative feedback. This research and development (R&D) study employed the ADDIE model, consisting of Analysis, Design, Development, Implementation, and Evaluation stages. The product was an Adobe Flash-based interactive educational game containing learning material, interactive quizzes, puzzles, drag-and-drop activities, and a matching game. Subjects were 28 fifth-grade students of SDN 19 Pulai, one IPAS teacher, and two expert validators. Data were collected through validation questionnaires, practicality questionnaires, and pretest-posttest scores, then analyzed descriptively using percentage categorization and the N-Gain formula. Results showed the media-expert validation reached 92% and the material-expert validation 93%, both categorized as very valid. The student practicality test averaged 95% (very practical), while the teacher’s response reached 96%. The effectiveness test showed the mean score rising from 68 (pretest) to 88 (posttest), with an N-Gain of 0.62, categorized as effective. These findings indicate that the developed digital assessment is valid, practical, and effective for IPAS learning in elementary school.